Biochar improves fertility of a clay soil in the Brazilian Savannah: short term effects and impact on rice yield - Carvalho, M.T.M.; Madari, Beáta E; Bastiaans, L.; Oort, P.A.J. van; Heinemann, Alexandre B.; Silva, M.A.S. da; Maia, A.H.N.M.; Meinke, Holger (2013)
The objective of this study was to report single season effects of wood biochar (char) application coupled with N fer_x0002_tilization on soil chemical properties, aerobic rice growth and grain yield in a clayey Rhodic Ferralsol in the BrazilianSavannah. Char application effected an increase in soil pH, K, Ca, Mg, CEC, Mn and nitrate while decreasing Alcontent and potential acidity of soils. No distinct effect of char application on grain yield of aerobic rice was observed.We believe that soil properties impacted by char application were inconsequential for rice yields because neither wa_x0002_ter, low pH, nor the availability of K or P were limiting factors for rice production. Rate of char above 16 Mg ha −1reduced leaf area index and total shoot dry matter by 72 days after sowing. The number of panicles infected by riceblast decreased with increasing char rate. Increased dry matter beyond the remobilization capacity of the crop, andhigh number of panicles infected by rice blast were the likely cause of the lower grain yield observed when more than60 kg N ha−1 was applied. The optimal rate of N was 46 kg ha−1 and resulted in a rice grain yield above 3 Mg ha−1.